Adjustment Outcomes of Native and Immigrant Youth in Spain: A Mediation Model. (1st June 2018) - López-Rodríguez, Lucía; Navas, Marisol; Cuadrado, Isabel; Tatar, Moshe
Abstract: This work proposes a conceptual model of psychological adjustment of native and immigrant adolescents who live in Spain. Psychological adjustment was expected to mediate between perceived family support and adolescents' school adjustment and problem behaviors. Spanish adolescents ( n = 156) and immigrant adolescents ( n = 137) filled out a self-report questionnaire regarding their perceived family support, psychological adjustment (i.e., self-esteem and life satisfaction), school adjustment, and problem behaviors. Structural Equation Modeling (SEM) was used to examine the relational patterns among these variables. The specific model –with psychological adjustment mediating between family support and school adjustment ( z = 2.70, β = .21, p = .007 for Spanish adolescents, and z = 2.42, β = .16, p = .015 for immigrant adolescents), and school adjustment mediating between psychological adjustment and problem behaviors ( z = –2.51, β = –.14, p = .012 for Spanish adolescents, and z = –2.01, β = –.11, p = .044 for immigrant adolescents) was confirmed for both samples. An implication of this study is the relevance of adolescents' family support to their well-being, and the mediating role of psychological adjustment between family support and school adjustment.